Ring-Over-Ring Deslipping From Imine-Bridged Heterorotaxanes - Hoshino, Sayaka; Ono, Kosuke; Kawai, Hidetoshi (Frontiers in Chemistry, 2022)
Ring-over-ring slippage and ring-through-ring penetration are important processes in the construction of ring-in-ring multiple interlocked architectures. We have successfully observed “ring-over-ring deslipping” on the rotaxane axle by exploiting the dynamic covalent nature of imine bonds in imine-bridged heterorotaxanes R1 and R2 with two macrocycles of different ring sizes on the axle. When the imine bridges of R1 were cleaved, a hydrolyzed hetero[4]rotaxane [4]R1′ was formed as an intermediate under dynamic equilibrium, and the larger 38-membered macrocycle M was deslipped over the 24-membered ring (24C8 or DB24C8) to dissociate into a [3]rotaxane [3]R3 and a macrocycle M. The time dependent NMR measurement and the determined thermodynamic parameters revealed that the rate-limiting step of the deslipping process was attributed to steric hindrance between two rings and reduced mobility of M due to proximity to the crown ether, which was bound to the anilinium on the axle molecule.